CEBPA double‐mutated acute myeloid leukaemia harbours concomitant molecular mutations in 76·8% of cases with TET2 and GATA2 alterations impacting prognosis. (25th March 2013) - Grossmann, Vera; Haferlach, Claudia; Nadarajah, Niroshan; Fasan, Annette; Weissmann, Sandra; Roller, Andreas; Eder, Christiane; Stopp, Elisa; Kern, Wolfgang; Haferlach, Torsten; Kohlmann, Alexander; Schnittger, Susanne
Summary Acute myeloid leukaemia (AML) with CEBPA mutations is listed as a provisional entity in the current World Health Organization classification. A difference in clinical outcome between single‐ (sm) and double‐mutated (dm) cases has been reported, whereupon CEBPAdm cases were shown to be associated with better overall survival (OS). The occurrence and prognostic impact of concomitant molecular mutations in addition to CEBPAdm has not been assessed until now with exception of GATA2 mutations. Here, we investigated a cohort of 95 AML CEBPAdm cases for concomitant mutations. TET2 was found to be most frequently mutated (34·0%) gene, followed by GATA2 (21·0%), WT1 (13·7%), DNMT3A (9·6%), ASXL1 (9·5%), NRAS (8·4%), KRAS (3·2%), IDH1/2 (6·3%), FLT3‐internal tandem duplication (6·3%), FLT3‐tyrosine kinase domain (2·1%), NPM1 (2·1%), and RUNX1 (1/94). Patients harbouring additional mutations in the TET2 gene showed significantly worse OS than TET2 wild‐type cases (P = 0·035), whereas GATA2‐mutated patients showed improved OS (P = 0·032). Serial analyses were performed for 39 CEBPAdm cases with concomitant mutations. Here, we observed that CEBPA mutations present the primary pathogenetic event in the majority of cases (76·9%). Further, a distinct gene expression profile (GEP) was confirmed for CEBPAdm versus CEBPAsm or CEBPA wild‐type cases while no significant changes in GEP were observed related to additional mutations within the CEBPAdm AML.